Cerebral Oxygenation Monitoring During Coronary Artery Bypass Grafting and Its Correlation with Hematocrit, Mean arterial pressure, and Partial pressure of Oxygen in Arterial Blood - Sharma, Jai; Verma, Indu; Agarwal, Swati; Dagar, Nivedita (Faculty of Medicine-Universitas Airlangga, 2025)
Introduction: Optimal cerebral oxygenation is vital during coronary artery bypass grafting (CABG) to prevent neurological complications like cognitive decline and stroke. Non-invasive monitoring methods include near-infrared spectroscopy (NIRS), electroencephalography (EEG), and transcranial doppler (TCD). It offers real-time rSO2 assessment, detecting critical thresholds and reducing risks during cardiopulmonary bypass (CPB). Objective: This observational study aims to investigates cerebral oxygenation changes during CABG and correlations with hematocrit, mean arterial pressure (MAP), blood oxygen levels, CPB flows, and temperature. Methods: Seventy-two elective CABG patients underwent CPB with parameters including rSO2, hematocrit, MAP, PaO2, temperature, and pump flows assessed at specific time points: T1: Baseline pre-anesthesia; T2: Post-anesthesia induction (FiO2 100%); T3: Post-anesthesia induction (FiO2 50%); T4: CPB initiation; T5: CPB at 35°C; T6: CPB at 32°C; T7: CPB rewarming (36°C); T8: Post-CPB weaning (FiO2 100%); T9: Post-CPB weaning (FiO2 50%). Results: The mean baseline values for rSO2 were 72.14 for the right side and 71.90 for the left side. Upon initiating CPB at 35°C, a significant maximum reduction in rSO2 of 10.5% was observed, which remained below baseline during the hypothermia phase. The rSO2 values began to increase during the rewarming phase, nearly reaching baseline levels after CPB. A post hoc analysis indicated that changes in rSO2 were correlated with variations in hematocrit (correlation coefficient = 0.518), MAP (correlation coefficient = 0.399), and PaO2 (correlation coefficient = 0.001). Conclusion: This study explored the fluctuations in rSO2 during CABG with CPB and examined its correlations with hematocrit, MAP, PaO2, CPB flows, and temperature. The findings highlight significant correlations among these variables, providing insights into factors influencing cerebral oxygenation during cardiac surgery.